2001
DOI: 10.1016/s0090-4295(01)01274-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of erectile dysfunction: results of the Brazilian study of sexual behavior

Abstract: The results of our study show that ED is a major health problem in Brazil and both the severity and prevalence increase with age. The medical, sociodemographic, and lifestyle variables associated with ED may alert physicians to patients who are at risk of ED, as well as offer clues to the etiology of ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
107
6
25

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(152 citation statements)
references
References 27 publications
14
107
6
25
Order By: Relevance
“…Studies carried out in other areas of the world show great variability. [2][3][4][5][6][7] Projections based upon these data may not best describe the problem of ED in either Egyptian, African, Asian or Arabic men living in their native countries. In the current study, we evaluated ED prevalence in a cross-sectional community-based study in Egypt.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies carried out in other areas of the world show great variability. [2][3][4][5][6][7] Projections based upon these data may not best describe the problem of ED in either Egyptian, African, Asian or Arabic men living in their native countries. In the current study, we evaluated ED prevalence in a cross-sectional community-based study in Egypt.…”
Section: Discussionmentioning
confidence: 99%
“…Liver disease occurred in 23 cases with eight receiving no treatment in the last 6 months. Three had surgery: portosystemic shunt (1) and splenectomy (2). We had 33 patients with renal disease including medical and surgical conditions, four of them had surgery for excision of bladder ulcer (1), nephrectomy (1), pyelolithotomy (1) and abdominal exploration after RTA.…”
Section: Erectile Dysfunction In Egyptian Menmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the MMAS had no direct measure of ED, depending, instead, on a derived variable constructed post hoc in a clinical convenience sample. 25 A large population-based survey in Brazil, 26 using the same ED assessment we employed, reported a prevalence of 18% for complete=moderate ED in men aged 40 -70 y.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies have involved the populations of industrially developed nations around the world, particularly in Europe, [1][2][3] and in the Americas. [4][5][6][7][8][9][10][11][12] The prevalence of the male sexual problems of erectile dysfunction and early ejaculation and their related risk factors have been investigated most extensively, whereas fewer studies have focused specifically on female sexual dysfunction. 13,14 Moreover, relatively little is known about the average frequency of sexual activity and the importance of sexual relationships among older men and women, although the few studies that have examined sexuality in mature adults have reported that sexual interest and activity persist well into older age.…”
Section: Introductionmentioning
confidence: 99%